The Effect of an 8-Week Online High-Intensity Interval Training Program on Body Composition and Performance in Thai Professional Football Players During the Covid-19 Epidemic - Wattana Nuttouch; Poramet Hemarachatanon; Soontaraporn Huntula (OVS LLC, 2023)
Background/objectives. High-intensity interval training (HIIT) was used to be a strategy for improving physical performance. Especially, athletic training which were disturbed by the Covid-19 pandemic. Therefore, the objectives of this study were to determine the effects of an 8-week online HIIT program on the body composition, aerobic and anaerobic performances in professional football players. Materials and methods. Thirty professional football players in Thai league division 2 were randomly assigned into the onsite group (n = 15) and the online group (n = 15). All participants performed the HIIT program at 85% maximal heart rate (HRmax), five times a week for 8 weeks. Body composition, aerobic and anaerobic performance at baseline, after 4 weeks and 8 weeks of training were calculated by repeated measures ANOVA and unpaired t-test. Results. Weight, BMI and % fat were significantly decreased after 4 weeks of training in the onsite group and after 8 weeks of training in the online group (p < 0.05). FFM in the onsite and online groups was significantly increased after 4 weeks and 8 weeks of training, respectively (p < 0.05). Aerobic performance was significantly increased after 4 and 8 weeks of training (p < 0.05), whereas anaerobic performance was found increased after 8 weeks of training in both groups (p < 0.05). There were no significant differences between the groups. Conclusions. Eight weeks of HIIT training can improve body composition, aerobic performance and anaerobic performance in both onsite and online conditions. It may be implied that an online HIIT training program should have beneficial effects similar to those provided in onsite condition.